ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL MULTIGRAVIDA DI PUSKESMAS BATURADEN II - Etika Dewi Cahyaningrum; Yuli Eko (Universitas Harapan Bangsa Purwokerto, 2009)
This background still discuss about a problem of anemia in women Indonesia as a result of iron deficiency. Anemia in pregnancy is anemia causedout of iron substance. Purpose of this study to determine the influence of thefactors that influence the incidence of anemia in pregnant women at CommunityHealth Centres (Pukesmas) Multigravida Baturaden II District Banyumas.Thisresearch method is quantitative descriptive method with cross sectional approach.Sampling technique used is total sampling. The amount of sample in this researchare 24 peoples.Conclusions of this study are the nutritional status, educationallevel, socio economics and level of knowledge has an influence on the incidence ofanemia. Birth spacing has no effect on the incidence of anemia. Keywords :analysis factors, anemia, multigravida